FORMATION AND DEVELOPMENT OF PHARMACEUTICAL EDUCATION IN KHARKIV - Tatiana Melentyeva; Oksana Kulakova ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The paper analyzes the documents of the formative education meetings, the resolutions of the People's Commissariat of Health Care in Ukraine, resulted the creation of plans for preparation of pharmacists and opening of the first pharmaceutical institute in Ukraine. The basic stages of development of pharmaceutical institute and changes in the program of training of specialists are considered. Changes in the forms of organization of the educational process have been observed.